Imprezy biegowe w Polsce – fenomen, nowy typ kibica, wpływ na postawy wobec aktywności fizycznej = Running Events in Poland - a phenomenon, a new type of fan, the impact on attitudes toward physical activity - Poczta, Joanna; Malchrowicz-Mośko, Ewa (Journal of Education, Health and Sport, 2015)
Poczta Joanna, Malchrowicz-Mośko Ewa. Imprezy biegowe w Polsce – fenomen, nowy typ kibica, wpływ na postawy wobec aktywności fizycznej = Running Events in Poland - a phenomenon, a new type of fan, the impact on attitudes toward physical activity. Journal of Education, Health and Sport. 2015;5(12):450-464. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35669 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A450-464 http://pbn.nauka.gov.pl/works/684629 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 15.12.2015. Accepted: 23.12.2015. Imprezy biegowe w Polsce – fenomen, nowy typ kibica, wpływ na postawy wobec aktywności fizycznej Running Events in Poland - a phenomenon, a new type of fan, the impact on attitudes toward physical activity Joanna Poczta, Ewa Malchrowicz-Mośko Zakład Kulturowych Podstaw Turystyki Wydział Turystyki i Rekreacji Akademia Wychowania Fizycznego im. E. Piaseckiego w Poznaniu Department of Cultural Foundations of Tourism Tourism and Recreation Faculty University School of Physical Education in Poznan Streszczenie Celem artykułu jest wykazanie, że wielkie wydarzenia biegowe takie jak maratony czy półmaratony zyskują coraz większą popularność zarówno pośród czynnych jak i biernych uczestników (kibiców) oraz określenie typu kibica imprez biegowych w Polsce. Badania przeprowadzone podczas 6. Poznań Półmaratonu oraz analiza danych wtórnych wykazały wzrastające zainteresowanie Polaków bieganiem oraz umożliwiły określenie nowego społeczno-demograficznego profilu kibica imprez biegowych. Słowa kluczowe: bieganie, kibice, turystyka sportowa. Abstract The main goal of this article is to prove that Polish cross-country events, such as marathons and half marathons are becoming increasingly popular among both active and passive participants (fans) and to determine the type of fan running events in Poland. Studies conducted during the 6th Poznan Half Marathon and analysis of secondary data have shown increasing interest of running by the Poles and noted the new profile fan running events. Keywords: running, fans, sports tourism.